2015
DOI: 10.1177/0003489415596755
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Assessment of Swallowing After Prolonged Intubation in the ICU Setting

Abstract: This study found a high frequency of dysphagia after prolonged intubation in patients with no preexisting dysphagia. Important variables leading to dysphagia are often overlooked, such as swallowing delay and laryngeal pathology. The timing of swallowing assessments did not reveal any difference in dysphagia frequency, suggesting that it might not be necessary to wait to perform dysphagia screens or evaluations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
79
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 34 publications
4
79
0
5
Order By: Relevance
“…There is no clear consensus about the timing of swallowing evaluations, with times varying among reports from immediately after to 48 h after extubation. As has been reported, the timing of swallowing evaluations is not correlated with the incidence of dysphagia (Scheel et al, ). In this study, we performed the swallowing screening at 4·9 h (median) after extubation, and no complications occurred from the swallowing evaluation.…”
Section: Discussionmentioning
confidence: 82%
“…There is no clear consensus about the timing of swallowing evaluations, with times varying among reports from immediately after to 48 h after extubation. As has been reported, the timing of swallowing evaluations is not correlated with the incidence of dysphagia (Scheel et al, ). In this study, we performed the swallowing screening at 4·9 h (median) after extubation, and no complications occurred from the swallowing evaluation.…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies have shown that up to 60% of ARF survivors are at risk for aspiration after extubation. Up to 25% aspirate “silently,” without signs on clinical exam[28]. Aspiration is associated with pneumonia, feeding tube and tracheostomy placement, longer ICU and hospital stay, and increased hospital mortality[9–16].…”
Section: Introductionmentioning
confidence: 99%
“…None focused exclusively on ARF survivors. Suggested mechanisms for aspiration after mechanical ventilation include “unlearning” of muscle memory, residual sedative medication effects, and injury to the mucosa or peripheral nerves from the endotracheal tube[8, 1923]. Due to differing mechanisms of aspiration in other populations, some predictive components of BSE may not apply to ARF survivors[2427].…”
Section: Introductionmentioning
confidence: 99%
“…The 1000–1500 mL of saliva produced daily may transiently be present in the oral cavity . Pooling of secretions in the pharyngolaryngeal region can be minimized by the normal swallowing function.…”
Section: Discussionmentioning
confidence: 99%
“…Fibreoptic endoscopic evaluation of swallowing (FEES) is widely used by speech‐language pathologists and otolaryngologists . FEES enables direct observation of the test food accumulating in the pyriform sinuses or entering below the vocal cords.…”
Section: Introductionmentioning
confidence: 99%